MAGNETORESISTENCIA TUNEL EN JUNTURAS CON MANGANITAS TUNNELING - Alvarez-Miño, Lucero (MOMENTO, 2010)
This paper reviews the tunnelling magnetoresistance (TMR) of magnetic tunneling junctions, particulary of those made of manganites. The origin of this type of tunneling and its dependence on the material, the growing method and the temperature are presented. Besides, some results on the influence of the half-metallicity and of the interfaces on the TMR are discussed.